2008
DOI: 10.1007/s11119-008-9081-1
|View full text |Cite
|
Sign up to set email alerts
|

Field-scale validation of an automated soil nitrate extraction and measurement system

Abstract: One of the many gaps that needs to be solved by precision agriculture technologies is the availability of an economic, automated, on-the-go mapping system that can be used to obtain intensive and accurate 'real-time' data on the levels of nitrate nitrogen (NO 3 -N) in the soil. A soil nitrate mapping system (SNMS) has been developed to provide a way to collect such data. This study was done to provide extensive field-scale validation testing of the system's nitrate extraction and measurement sub-unit (NEMS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…At the crop level, the aim is to improve N management through various complementary fertilization strategies and soil management regimes such as precision fertilization through split fertilizer strategies (Van Alphen and Stoorvogel 2000;Hirel et al 2011) or fertilizer placement strategies (Burns et al 2010). Modeling the N demand during crop growth is one of the tools to support precision fertilization to adjust application timing and placing of N based on measurements of plant material (such as petiole tests), measurements of soil conditions (available N), or both (Sibley et al 2009(Sibley et al , 2010Schröder 2014), together with predictions of future gain in dry matter (De Koeijer et al 1999). …”
Section: Recent Developments In the Agronomy Of Nitrogen Use Efficiencymentioning
confidence: 99%
“…At the crop level, the aim is to improve N management through various complementary fertilization strategies and soil management regimes such as precision fertilization through split fertilizer strategies (Van Alphen and Stoorvogel 2000;Hirel et al 2011) or fertilizer placement strategies (Burns et al 2010). Modeling the N demand during crop growth is one of the tools to support precision fertilization to adjust application timing and placing of N based on measurements of plant material (such as petiole tests), measurements of soil conditions (available N), or both (Sibley et al 2009(Sibley et al , 2010Schröder 2014), together with predictions of future gain in dry matter (De Koeijer et al 1999). …”
Section: Recent Developments In the Agronomy Of Nitrogen Use Efficiencymentioning
confidence: 99%
“…It was found that the electrode responded equally well regardless of whether the NO 3 -N level was changing from lower to higher, or higher to lower during measurement. Nested linear regression analyses revealed that the NEMS had the same level of performance over all field conditions tested regardless of what data processing method was used (Sibley et al, 2009). It was concluded that any of the regression equations developed for describing the relationship between NEMS measurements and Lab measurements for the four data processing methods tested (Fig.…”
Section: Experiments Conducted To Validate In-field Measurements Of Smentioning
confidence: 94%
“…Following field calibration, soil samples can be collected and analyzed for NO 3¯ every 40 seconds (6 seconds for NO 3¯ analysis and 34 seconds for other mechanical system functions to cycle). Sibley et al (2009) has found this y/x routine sufficient for field use. After field calibration, soil samples can be collected and analyzed for NO 3¯.…”
Section: Operation Of the Nitrate Extraction And Measurement Sub-unitmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to measurement accuracy, a key issue is the number of sampling points and the spatial resolution of the measurements. The development of "on-the-go" sensors is of primordial importance (Viscarra Rossel&McBratney 1998b) and considerable research efforts have been devoted to the development of fast, fully automated and geo-referenced measurement systems (Sibley et al 2009;Mouazen et al 2007;Christy 2008;Adamchuk et al 2004Adamchuk et al , 2005Sinfield et al 2010). Among the spectroscopy-based methods, the use of NIR has been investigated more actively, mostly due to the lower price and higher robustness of the equipment.…”
Section: On-the-go Sensing and Combination With Gismentioning
confidence: 99%